2010
DOI: 10.1063/1.3469719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pb and Cr Substitutions on Phase Formation and Excess Conductivity of Bi-2212 Superconductor

Abstract: Articles you may be interested inSynthesis of BiSrCa(Y)CuO superconductor from the sol-gel method and the effect of Y substitution AIP Conf. Scaling of the vortex-liquid resistivity and temperature and magnetic field dependent activation energy in Ho doped (Bi, Pb)-2212 superconductor Abstract. The influence of Pb and Cr substitutions on the superconducting properties of Bi 2 Sr 2 CaCu 2 O 8 (Bi-2212) superconductors is reported. The samples were prepared from Bi 2 -xPbxSr2Ca2-yCryCu3O10- (x=0-0.3, y=0-0.3) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several types of Bi-2212 samples were already analyzed by means of excess conductivity/fluctuation-induced conductivity in the literature. This comprises single crystals [62] polycrystalline bulks [63][64][65], polycrystalline Bi-2212 doped with Ni, La [66][67][68], and Bi-2212 thin films [69]. Several authors found the missing 1D fluctuation regime in their Bi-2212 samples, and a similar observation was made when studying the Y-358 compound [70].…”
Section: Discussionmentioning
confidence: 68%
“…Several types of Bi-2212 samples were already analyzed by means of excess conductivity/fluctuation-induced conductivity in the literature. This comprises single crystals [62] polycrystalline bulks [63][64][65], polycrystalline Bi-2212 doped with Ni, La [66][67][68], and Bi-2212 thin films [69]. Several authors found the missing 1D fluctuation regime in their Bi-2212 samples, and a similar observation was made when studying the Y-358 compound [70].…”
Section: Discussionmentioning
confidence: 68%